Mekanisme Pemberian Izin Mendirikan Bangunan Bagi Pembangunan Perumahan - Zegovia Parera; Abrar Saleng (Batulis Civil Law Review, 2021)
This study aims to identify and analyze statutory regulations related to building permits for the implementation of the conversion of protected areas into residential buildings and to analyze the control of spatial use of housing development in Merauke District. This research is an empirical legal research. This research was conducted at the Legal Division of the Merauke Regency Regional Secretariat, the Spatial Planning Section of the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency of Merauke Regency, the Public Works and Spatial Planning Office of Merauke Regency, developers, and residential communities. The results of this study indicate that the laws and regulations related to building permits on the implementation of housing development are an obligatory affair of the regency / city government, in this case the management of buildings, which includes setting up building permits (IMB) and certificates of eligibility for building functions (SLF). new. As well as the implementation of the function change of protected areas in Samkai Village is not in accordance with the current spatial direction. For this reason, the local government of Merauke Regency is within its authority to regulate and balance the arrangement of buildings in conservation areas and water catchment areas so that the community has permits to build buildings according to the regulations. And Controlling Spatial Use of Housing Development in Protected Areas Local governments still face various obstacles / obstacles, namely not having a regional regulation on a strategic plan (renstra) for protected areas so that the government has not been able to provide certainty to the public regarding the activity plan and financing of the housing location. Supervision and control are still passive in nature because they are only based on complaints and are not carried out regularly. Most of the land in the protected area belongs to the private sector and the community, so that control is limited to an appeal.